Higher Sensitivity of Deep Soil Root Productivity to Precipitation Changes - Xinxing Huo; Bingwei Zhang; Philippe Ciais; Yiqi Luo; Changhui Peng; Yuhong Tian; Xiuchen Wu (Global Ecology and Biogeography, 2025)
Aim Plastic responses of root productivity to precipitation changes would facilitate plant survival under drought stress. However, whether the responses are pervasive along the soil profile remains unknown. Here, we compiled a global dataset of root productivity at different soil depths from in situ precipitation manipulation experiments, and investigated whether the root productivity responded to precipitation changes uniformly or nonuniformly along the soil profile across diverse biomes. Location Global. Time Period Studies published during 2000–2022. Major Taxa Studied Mature woody plants and herbaceous. Methods Meta‐analysis was conducted to evaluate the responses of root productivity at different soil depths to precipitation changes. The partial least squares path model (PLS‐PM) was used to explore the pathways how various biotic and abiotic factors regulate these responses at different soil depths and across different vegetation types. Results Root productivity responded divergently to decreased precipitation between surface and deep soil. Decreased precipitation significantly reduced root productivity in surface soil (effect size: −0.19 ± 0.05), but significantly increased root productivity in deep soil (effect size: 0.18 ± 0.13), particularly under long‐term (> 3 years) and severe (> 50% reduction in precipitation) drought treatments. Increased precipitation stimulates root productivity in all soil layers, with increasing stimulation towards deep soil depth. Main Conclusions This study highlights higher sensitivity of deep soil root productivity to precipitation changes, providing crucial insights into potential shifts in ecosystem belowground structure and functioning in a more extreme climate regime.